THE RELATIONSHIP BETWEEN UNIVERSITY STUDENT ABOUT EDUCATIONAL MECHANICAL ENGINEERING WORKSHOP TO MOTIVATION IN FOLLOWING THE PRACTICAL WORK OF MECHANICAL PRODUCTION AT ACADEMIC YEAR 2016/2017 - Francisko; Wiyogo (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
This research aims to discover whether the positive correlation and significance between student’s perception about the educational mechanical engineering workshop to motivation in following the practical production process at academic year 2016/2017. The one of factors influencing the student’s motivation is perception to mechanical workshop paradigm in which many students stated that practical work is less maximum during implementation. Furthermore, several students showed then less motivation signed less providing own attention to instructor. In this research, it uses the survey type involving data collection method is utilizing the questionnaire and interview. The research subject is university students of 2011/2012/2013 with sample total is 61 students. The data analysis used the moment product correlation. The analysis prerequisite tests are normality test and linearity test followed by SPSSV to be analysis prerequisite test. The result performed that there the positive relationship and significance between student’s perception about mechanical engineering workshop to motivation in attending production process at academic year 2016/2017. It is proved by correlation coefficient value Rxy at about 0.927 and tcount at around 1.985 higher than ttable having value at 1.671 on significance level 0.05.